Human zygote reconstruction by spindle, polar body or pronuclear transfer to treat repeated embryo fragmentation or embryo developmental arrest: The future is now - Konstantinos A Economou (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2018)
A common and very difficult issue to overcome as a clinical embryologist during an IVF cycle is the event of severe embryonic fragmentation or, more rarely, full developmental arrest. The current approach to bypass these phenomena is oocyte donation, but this raises several ethical concerns from the couple's side, since the offspring will bear only 50% of the biological characteristics of the parents. Apart from spindle and polar body transfer, the emerging technique in order to overcome these obstacles is called Pronuclear Transfer (PNT). PNT is safest to perform with improved results than spindle or polar body transfer. In PNT, the two parental pronuclei are being transferred into a donor's enucleated zygote and after a fusion process has been achieved, the newly constructed embryo may result into a newborn bearing both the paternal and maternal biological characteristics. This process opens a whole new horizon in assisted reproduction and will probably replace the traditional oocyte donation in the form we know it today.